C# 7 and .NET Core 2.0 High Performance : Build highly performant, multi-threaded, and concurrent applications using C# 7 and .NET Core 2.0. - Mehboob Ahmed Khan, Ovais (Packt Publishing, 2018)
Performance tuning for real-world applications often involves activities geared towards finding bottlenecks, however this alone cannot solve the dreaded problem of slow code. If you want to improve the speed of your code and optimize the performance of your apps, then this book is for you.